Risk of emergency cesarean section when giving birth in Sweden: A nationwide cohort study comparing women born in countries practicing female genital mutilation, with Swedish-born women - Eshraghi, Bita; Hermansson, Jonas; Marions, Lena (PLOS ONE, 2025)
Introduction The impact of female genital mutilation (FGM) on obstetric outcomes in high-income countries remains unclear and is an area of ongoing research. This nationwide study aimed to examine the risk of emergency cesarean section among primiparous women from countries where FGM is practiced, in comparison to Swedish-born women. Additionally, the study explored whether a confirmed diagnosis of FGM contributes to this potential risk. Materials and methods A Swedish nationwide cohort study including primiparous singleton term deliveries (≥37 + 0– < 42 + 0 weeks) during 2014–2020. Data was extracted from the Swedish Medical Birth Register and the National Patient Register. We compared the risk of emergency cesarean section between women born in an FGM-practicing country and women born in Sweden by using multivariable logistic regression. Two subgroup analyses were performed. Results Women born in FGM-practicing countries (n = 13 246) had a significantly increased risk of emergency cesarean section (aOR 1.28, 95% CI: 1.21–1.35) compared to Swedish-born women (n = 199 914). Including FGM diagnosis as a covariate did not alter the result. When excluding women born in FGM-practicing countries outside Sub-Saharan Africa the aOR was amplified (aOR 1.58, 95% CI: 1.47–1.69). To further isolate the effect of FGM itself, we restricted the analysis to women born in FGM-practicing countries and compared those with a recorded FGM diagnosis to those without. This analysis showed no significant association between FGM diagnosis and emergency cesarean section (aOR 1.05, 95% CI: 0.90–1.23). Conclusions Primiparous women from FGM-practicing countries have an increased risk of emergency CS compared to Swedish-born women, when giving birth in Sweden. The presence of FGM diagnosis did not contribute to this risk. Further research is needed to understand the underlying mechanisms for this to be able to improve obstetric care for migrant populations.